Optimizing multiplex PCR for a set of Malay ancestry informative marker single nucleotide polymorphisms and preliminary analysis of genotypes between Malay and non-Malay population - Yi-Ting, Cheng (2021)
Introduction Inference of ancestry is of great interest to many and various methods have been developed in selecting and validating panels of ancestry informative markers (AIMs). One of the ancestry informative marker that is commonly used is single nucleotide polymorphisms (SNPs). Yahya et al, 2017 had determined that a panel of approximately 200 SNPs can distinguish the Malay population with an accuracy of more than 80%. Five SNPs were chosen from the above panel of SNPs to be developed into a PCR-multiplex assay. This pilot study describes the PCR optimization process and the genotyping results of the Malay and non-Malay subjects. Methodology Ancestry informative marker SNP panels were selected from the genotyping databases of the Malaysian Node of the Human Variome Project and Singapore Genome Variation Project and referenced against the International HapMap Project Phase 3. Five SNPs were chosen for the pilot study (rs197824, rs752625, rs4599414, rs12550668 and rs4134376). The subjects were participants who identified themselves as Malay and non-Malay for at least 3 generations. Forward and reverse primers were designed for each SNP and the polymerase chain reaction (PCR) for each SNP were optimized in singleplex. The PCR products were then sequenced to determine the allele at the target SNP. Results and Discussion Four SNPs were successfully optimized and later genotyped for 10 subjects. The difference in the genotypes of the Malay and non-Malay populations were found to be statistically insignificant, however, there is a significant difference in the allele frequency for rs752625. One SNP rs4134376 was tri-allelic. The similarities may arise from several factors, including the history of admixture in these populations that have occurred, the close geographical distance, and the absence of appropriate reference population. To validate the panel further, more SNP and more subjects should be involved, and genotyping could be done with single base extension reaction in multiplex to assay multiple SNPs simultaneously.